2016
DOI: 10.1371/journal.pone.0163093
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Salt Added to Takeaway Food: Within-Subjects Comparison of Salt Delivered by Five and 17 Holed Salt Shakers in Controlled Conditions

Abstract: ObjectivesTo determine if the amount of salt delivered by standard salt shakers commonly used in English independent takeaways varies between those with five and 17 holes; and to determine if any differences are robust to variations in: the amount of salt in the shaker, the length of time spent shaking, and the person serving.DesignFour laboratory experiments comparing the amount of salt delivered by shakers. Independent variables considered were: type of shaker used (five or 17 holes), amount of salt in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The present findings, that were derived from a real-world experiment, show that making minor changes to daily food environments can lead to positive effects on sugar intake in habitual behaviors. Modifying the functional design of sugar shakers resulted in a reduction of the amount of added sugar of 19.75% compared to the default condition, which strengthens the results on table salt use [ 7 – 10 , 15 ] and adds to the evidential basis that reducing dispensed quantities can sustainably change individual behaviors in public places.…”
Section: Discussionsupporting
confidence: 61%
“…The present findings, that were derived from a real-world experiment, show that making minor changes to daily food environments can lead to positive effects on sugar intake in habitual behaviors. Modifying the functional design of sugar shakers resulted in a reduction of the amount of added sugar of 19.75% compared to the default condition, which strengthens the results on table salt use [ 7 – 10 , 15 ] and adds to the evidential basis that reducing dispensed quantities can sustainably change individual behaviors in public places.…”
Section: Discussionsupporting
confidence: 61%
“…Single-target interventions, with one nutritional focus, were rare. However, there was one widely cited example that involved replacing the 17-hole cap of a counter-top salt shaker with a 5-hole cap to reduce the amount of salt dispensed [ 32 , 33 ]. Multi-component interventions were more common, especially healthy catering award schemes.…”
Section: Resultsmentioning
confidence: 99%
“…Future work should look for opportunities to develop, deliver and evaluate covert (to the consumer) interventions. The 5-hole salt shaker is one such intervention, which we recently evaluated [ 32 , 33 ]. We concluded that their use is associated with lower relative sodium content of fish and chip meals [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Restricting the habit of adding salt to food at the table has been proposed to reduce salt intake [ 35 , 36 ]. Public health education or removing/replacing salt shakers could also partially reduce salt added at the table [ 4 , 37 , 38 ]. However, the habit of adding salt at the table is prevalent, whether in developed regions [ 3 5 ] or in low- and middle-income countries [ 12 , 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%